Compliance Analysis of Vaccine Storage and Distribution at the Samarinda Pharmacy Installation in December 2024 - Asih Rahayu Pamungkas; Muh. Taufiqurrahman; Raymon Simanullang (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Vaccines are very susceptible to damage, so vaccine management requires special handling. Vaccines if handled not according to the provisions can cause damage to the vaccine so that it reduces or eliminates the potential, and can even cause post-immunization adverse events when administered. The objective of this study is to assess the compliance of immunization vaccine storage and distribution at Samarinda Pharmacy Installation with the Good Distribution Practices (GDP) Guidelines of 2020 and Guidelines for Vaccine Management in Healthcare Facilities of 2021 for the period December 2024. This research approach is qualitative research. Qualitative research is presented in descriptive form. Data collection was carried out by observation using a checklist, document observation in 2024 and interviews with the pharmacist in charge. The population in this study were all immunization vaccines stored at the Samarinda Pharmacy Installation. The results obtained will be compared with the guidelines of good distribution practice and the guidelines for vaccine management in health facilities. Based on the results of the study conducted at Samarinda Pharmacy Installation, the compliance of vaccine storage was 67% based on the GDPN Guidelines of 2020 and 94% based on the Guidelines for Vaccine Management in Healthcare Facilities of 2021. The compliance rate of vaccine distribution was 83% based on the GDP Guidelines of 2020 and 100% based on the Guidelines for Vaccine Management in Healthcare Facilities of 2021.